1993
DOI: 10.1113/jphysiol.1993.sp019791
|View full text |Cite
|
Sign up to set email alerts
|

Response of sensory units with unmyelinated fibres to mechanical, thermal and chemical stimulation of the cat's cornea.

Abstract: SUMMARY1. In the cat anaesthetized with sodium pentobarbitone, electrical activity was recorded from single unmyelinated sensory fibres innervating the cornea.2. Based on their response to mechanical (calibrated aesthesiometer), chemical (10 mm acetic acid or 616 mm NaCl) and thermal (cooling from 35 to 5°C; heating to 51°C) stimuli, corneal unmyelinated fibres were classified as polymodal (71 %) or 'cold' nociceptors (29 %).3. Polymodal units responded to mechanical indentation of the cornea and developed fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
171
0
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(203 citation statements)
references
References 23 publications
18
171
0
3
Order By: Relevance
“…Thereafter, we used BCTC to explore the contribution of TRPM8 to cold-evoked electrical activity in the soma and peripheral nerve terminals of trigeminal ganglion (TG) neurons. Peripheral studies were performed in the cornea, a tissue with a dense innervation of cold thermoreceptors (Gallar et al, 1993;Carr et al, 2003). We conclude that, in the soma of the large majority of cultured trigeminal neurons, activation of TRPM8 channels is the major player in establishing cold-evoked responses.…”
Section: Introductionmentioning
confidence: 88%
“…Thereafter, we used BCTC to explore the contribution of TRPM8 to cold-evoked electrical activity in the soma and peripheral nerve terminals of trigeminal ganglion (TG) neurons. Peripheral studies were performed in the cornea, a tissue with a dense innervation of cold thermoreceptors (Gallar et al, 1993;Carr et al, 2003). We conclude that, in the soma of the large majority of cultured trigeminal neurons, activation of TRPM8 channels is the major player in establishing cold-evoked responses.…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, the responses of thermonociceptive neurons of both taxa were antagonized by capsazepine, an antagonist of the vanilloid receptor, VR1 (Marin-Burgin et al, 2000;Liu and Simon, 2000). Finally, polymodal nociceptors, an important class of neurons that respond to both noxious thermal and mechanical stimuli, are found in both taxa (Necker and Reiner, 1980;Gallar et al, 1993). However, although mammalian polymodal nociceptors are responsive to sub-micromolar concentrations of CAP (Liu et al, 1996), neural sensitivity to similar concentrations of CAP has not been observed in birds (Wood et al, 1988).…”
Section: Experiments 3 Ion Dependence Of Neuronal Sensitivitymentioning
confidence: 99%
“…Most of the suggested alternatives to the Draize test involve in vitro assays (Booman et al, 1989), though in vivo assays have also been proposed (e.g., Kennah II et al, 1989). One in vivo approach explored in animals has consisted of recording electrophysiological responses to instilled compounds from the sensory nerve fibers innervating the eye (Belmonte et al, 1991;Beuerman et al, 1992;Gallar et al, 1993).…”
Section: Introductionmentioning
confidence: 99%